Розвиток інституту авторизованого економічного оператора в Україні в контексті імплементації міжнародних стандартів - Микитенко, Тетяна Владиславівна; Мельник, Олена Володимирівна; Сагайдак, Ірина Степанівна (Видавничий дім «Гельветика», 2023)
У статті проаналізовано актуальні питання розвитку та функціонування інституту авторизованого економічного оператора в Україні та у світі. Розглянуто історію становлення інституту авторизованого економічного оператора. Досліджено вплив міжнародних стандартів, зокрема Рамкових стандартів безпеки Всесвітньої митної організації, на формування інституту АЕО. Досліджено сутність поняття «авторизований економічний оператор» для визначення його ролі й місця у формуванні безпечних ланцюгів постачання товарів на шляху імплементації міжнародних митних стандартів та розвитку національної економіки. Розглянуто особливості набуття статусу АЕО підприємствами та переваги, які він надає. Проаналізовано досвід України у запровадженні АЕО. Запропоновано напрями удосконалення інституту АЕО в Україні, зокрема: адаптація термінології, процедур оцінки відповідності підприємств, взаємне визнання статусів з ЄС. Зроблено висновок, що впровадження міжнародних стандартів щодо АЕО сприятиме активізації міжнародної торгівлі та підвищенню конкурентоспроможності українських підприємств.

This scholarly article conducts an examination of the current developmental stage and practical functionality of the Authorized Economic Operator (AEO) institution in Ukraine and internationally. It rigorously investigates the significant influence of the World Customs Organization's Framework of Standards on systematically shaping the intricate, multifaceted AEO framework. The particulars of enterprises endeavoring to attain the privileged AEO designation and the numerous far-reaching privileges it furnishes, including extensively streamlined customs processes and markedly accelerated regulatory clearances, are thoroughly explored utilizing empirical data. Ukraine's experience in instituting AEO protocols is meticulously scrutinized – as of 2023, only 21 companies have successfully acquired the status after an application process from a substantial pool of eager applicants. Numerous thought-provoking proposals to meaningfully optimize Ukraine's fledgling AEO system are put forward, encompassing: calibrating the scheme's elaborate legal vernacular to domestic exigencies, refining the company vetting procedures, and most critically - instituting reciprocal AEO recognition and close cooperation with the EU's mature AEO programs. Extensive statistical data from reputable global and domestic sources contrasts Ukraine's gradual AEO adoption rate compared to other nations' relatively expeditious success. Illustrative real-world case studies are furnished that demonstrate the difficulties Ukrainian firms routinely encounter throughout the taxing AEO certification process. The paper extols at length the paramount urgency of progressively harmonizing Ukraine's AEO laws and procedures with ambitious international benchmarks to potentially enable integration into Europe's vast economic bloc. Establishing mutual AEO status recognition between the EU and Ukraine is meticulously analyzed from multiple thoughtprovoking perspectives projected to be tremendously beneficial for both entities. This article cogently argues that implementing these multifarious international AEO standards in close coordination with European stakeholders will steadily streamline cross-border trade and meaningfully augment Ukrainian companies' global competitiveness, contingent on public-private collaboration. The suggested expansions substantially enhance the academic rigor and practical applicability of this timely treatise on the crucial AEO sphere.
Keywords: рамкові стандарти ВМО; авторизований економічний оператор; митні процедури; міжнародна торгівля; WMO framework standards; authorized economic operator; customs procedures; international trade